Piecewise linear processes with Poisson-modulated exponential switching times (2019)
We consider the jump telegraph process when switching intensities depend on external shocks also accompanying with jumps. The incomplete financial market model based on this process is studied. The Esscher transform, which changes only unobservable parameters, is considered in detail. The financial market model based on this transform can price switching risks as well as jump risks of the model. © 2019 John Wiley and Sons, Ltd.